A new semiterrestrial crab from limestone hills in Vietnam (Crustacea: Brachyura: Potamidae: Tiwaripotamon) - Ng, Peter K. L.; Tri, Ngo Van (Zootaxa, 2022)
A new species of semiterrestrial crab of the potamid genus Tiwaripotamon Bott, 1970, is described from limestone hills in northern Vietnam. Tiwaripotamon bellum n. sp. is one of the largest known species in the genus, and its external morphology is most similar to T. vietnamicum (Đăng & Hồ, 2002), described from northern Vietnam. Tiwaripotamon bellum n. sp., however, can easily be separated by its much darker colour in life, possession of a distinct epibranchial tooth on the carapace, the proportionately shorter ambulatory meri, and the gently curved terminal segment of the male first gonopod, with a subtruncate tip and dorsal lobe on the proximal part of the structure.